PENGARUH OTORITAS PENGAMBILAN KEPUTUSAN TERHADAP EFEKTIVITAS PENGELOLAAN SEKOLAH DI KOTA MATARAM - Abdul Kadir (Faculty of Economics, State University of Jakarta., 2016)
The school management effectiveness is significantly influenced by the role of local leaders, the school committee who runs its roles functionally, positive supports delivered by virtual teams and effective decisions made by the principal. 100 principals and 300 senior teachers of primary schools had filled out questionnaires.The data then analyzed statistically by applying path analysis. Research reveals that there are positive direct effects among the variables tested and it can be viewed from two major paths. Firstly, the school management effectiveness is directly influenced by the roles of local leaders, functioned school committee, supports by virtual team and decision making. Secondly, decision making directly influenced also by the roles of local leaders, functioned school committee, and supports by virtual team. It implies that the school management proved its effectiveness when attained direct positive roles from local leaders, functioned school committee, supports by virtual team and effective decision making handled by the principal.